2017
DOI: 10.1002/jbmr.3283
|View full text |Cite
|
Sign up to set email alerts
|

High Bone Turnover in Mice Carrying a Pathogenic Notch2 Mutation Causing Hajdu-Cheney Syndrome

Abstract: Hajdu-Cheney syndrome (HCS) is a rare autosomal-dominant disorder primarily characterized by acro-osteolysis and early-onset osteoporosis. Genetically, HCS is caused by nonsense or deletion mutations within exon 34 of the NOTCH2 gene, resulting in premature translational termination and production of C-terminally truncated NOTCH2 proteins that are predicted to activate NOTCH2-dependent signaling. To understand the role of Notch2 in bone remodeling, we developed a mouse model of HCS by introducing a pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
(112 reference statements)
4
19
0
Order By: Relevance
“…The mechanism involves a direct effect of Notch2 on osteoclast precursors as well as the induction of RANKL by cells of the osteoblast lineage. In an alternate murine model of HCS, an increased expression of interleukin 6 was reported in bone marrow cells, and this cytokine could contribute to the enhanced bone resorption observed [40]. Notch2 tm1.1Ecan mutant mice are sensitized to the development of osteoarthritis, a mechanism that may also involve an enhanced expression of interleukin 6 by the chondrocyte of HCS mutant mice [41].…”
Section: Notch and Congenital Disorders Of The Skeletonmentioning
confidence: 99%
“…The mechanism involves a direct effect of Notch2 on osteoclast precursors as well as the induction of RANKL by cells of the osteoblast lineage. In an alternate murine model of HCS, an increased expression of interleukin 6 was reported in bone marrow cells, and this cytokine could contribute to the enhanced bone resorption observed [40]. Notch2 tm1.1Ecan mutant mice are sensitized to the development of osteoarthritis, a mechanism that may also involve an enhanced expression of interleukin 6 by the chondrocyte of HCS mutant mice [41].…”
Section: Notch and Congenital Disorders Of The Skeletonmentioning
confidence: 99%
“…In recent mouse studies, LyzM-Cre mediated myeloid-specific Notch1 −/− Notch2 −/− Notch3 −/− triple knockout facilitates osteoblast formation and concomitantly impairs osteoclastogenesis (Bai et al, 2008). Other recent studies demonstrated that the Notch2 HCS mutant mice faithfully recapitulate the features of HCS (Canalis et al, 2016; Vollersen et al, 2017). Additionally, a recent case study reported that the administration of denosumab, a RANKL antagonist, increases bone mineral density in a patient with HCS (Adami et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
“…HCS is an ideal model to study a physiological function of NOTCH2 as C-terminal truncation mutations in HCS are shown to confer gain-of-function properties to Notch2 in mice (Canalis et al, 2017; Canalis et al, 2016; Vollersen et al, 2017). Moreover, most identified HCS NOTCH2 mutations cluster between the second nuclear localization signal (NLS) and the PEST domain, resulting in C-terminal premature truncation of NOTCH2 that lacks the PEST sequence (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work demonstrated that Notch2 DPEST/DPEST osteoblasts express increased levels of Tnfsf11 mRNA, suggesting that osteoblast-derived RANKL is responsible for the enhanced bone resorption in Notch2 tm1.1ECan mutant mice. 35,52,57 Similarly, a subject with HCS and severe osteoporosis was reported to present with elevated levels of RANKL in the serum. 18 Notch2 tm1.1ECan and control sex-matched littermates were subjected to splenectomies or sham interventions at 1 month of age and sacrificed 1 month later for analysis.…”
Section: Discussionmentioning
confidence: 97%